Management of knowledge and competence through human resource information system—A structured review - Memon, Khalid Rasheed; Ghani, Bilqees; Hyder, Syed Irfan; Han, Heesup; Zada, Muhammad; Ariza-Montes, Antonio; Arraño-Muñoz, Marcelo (Frontiers in Psychology, 2022)
The fourth industrial revolution will be ushered in by future high technology, and as a result, the world will face new difficulties relating to people, the environment, and profitability. Accordingly, the competitive edge and long-term viability of businesses would depend on the knowledge workers who could overcome these excruciatingly difficult obstacles and have the knowledge and competency to influence the overall performance of any type of company. But managing knowledge workers falls under the purview of human resources, and only effective human resources tools, plans, and procedures can ensure the success of this task. One such tool, which has the capacity and capability to change the whole scenario in an organization's favor, is the human resource information system (HRIS). The purpose of this structured review is to provide insight into a field of HRM (i.e., HRIS) that has largely been neglected by other reviews of the literature and has only been briefly discussed by a small number of publications published in reputable, top-tier journals. A customized HRIS framework is the result of this structured literature review for managing knowledge and competence. The study presents the content analysis of 48 articles, systematically and purposefully selected for this literature review, published during the past three decades. The study has several implications for policymakers and HR practitioners.